The effect of saving and capital expansion on financial and technological development in GCC countries - Alshubiri, Faris (Technological and Economic Development of Economy, 2022)
This study examined the effect of the relationship between saving and capital expansion on financial and technological development in three GCC countries using panel data from 1990 to 2019. The study used panel least squares, feasible general least squares, dynamic ordinary least squares and fully modified ordinary least squares used in the study. The findings showed that there was a significant positive long-run relationship between capital expansion and financial development and was a positive and insignificant long-run relationship between saving and financial development. Conversely, the study showed that there was a significant positive long-run relationship between saving and technological development. Meanwhile, there was a negative long-run relationship between capital expansion and technological development. Pairwise Granger causality test results showed that there was bidirectional causality between saving and financial development, a single causal direction from Adjusted net national income and financial development and a single causal direction from technological development and saving and Inflation, consumer prices. The main conclusions of the study were saving tends to support technological development, while investment tends to improve financial development. Therefore, GCC countries should formulate a long-term growth strategy in all sectors to determine their development requirements in light of the available resources.First published online 15 November 2021